Recursos didácticos para mejorar el aprendizaje en Estudios Sociales, séptimo grado “A” de la Escuela de EGB “Miguel Riofrío”, Loja, periodo, 2023-2024 - Loja Zhanay, Jennifer Araceli (2024)
The present research study is focused on didactic resources to improve learning in Social Studies. For which the following general objective was developed: To determine the impact generated by the didactic resources to improve learning in Social Studies, seventh grade “A” of the General Basic Education School “Miguel Riofrío”, period, 2023-2024. Three specific objectives were included in order to comply with the study, which were based on diagnosing the learning of Social Studies, proposing an alternative for its improvement and evaluating the current state of learning in this subject. In the methodological process, a mixed approach was used, since the impact generated by the implementation of didactic resources to improve learning in Social Studies was determined. In addition, it was of an exploratory-descriptive type, since it allowed to become familiar with the learning according to the object of study. A non-experimental transectional design was also used because the study variables were not manipulated, in this case the didactic resources and learning in Social Studies. Finally, the research was complemented with the following methods: scientific, analytical, synthetic, deductive, inductive and statistical, which contributed to establish the statements of the theoretical framework, to give veracity to the present research work. Likewise, a representative sample of 24 students of the seventh parallel grade “A” was taken as a survey and evaluation, and the teacher of the same grade was also taken into consideration and an interview was carried out. The most relevant results showed a significant improvement in the comprehension and retention of the contents of Social Studies. At the end of the study, the importance of using innovative teaching strategies to enhance student learning in this area is highlighted. Therefore, it is important to continue exploring and using new educational methodologies to strengthen the teaching and learning process in Social Studies.